Freedom of religion or belief-a human right under pressure - Bielefeldt, Heiner (Taylor and Francis, 2016)
Take, for instance, the various programmes of building consensus on theological or metaphysical grounds. A famous example is the treatisec De pace fidei5, written by Nicolaus Cusanus in 1453 shortly after the Fall of Constantinople.1 By constructing a fictitious dialogue among representatives of all major religions of his day Cusanus w anted to persuade his audience that existing differences between religions merely concern marginal issues. Cusanus went as far as to claim that all religions essentially coincide, thus ultimately form ing one single religion with a variety of different rituals-‘unareligio in rituum varietate5. Such an idea m ay sound familiar especially to mystics from various traditions. For instance, followers of Islamic Sufi orders have expressed similar views maintaining that the spiritual paths of all religions ultimately lead to one and same goal, with the result that remaining differences should not matter too much. In a somewhat different spirit, religious liberals in the age of the enlightenment, such as Diderot, Lessing or Kant, also pursued a programme of eradicating denominational conflicts by presenting metaphysical arguments for what they called the ‘natural religion5 underlying all historical religions.2 This enlightenment idea of the one natural religion could be used to unmask remaining denominational differences as meresocietal prejudices which, it was hoped, would gradually disappear.
CRIS-Team Scopus Importer:2023-03-21